2020
DOI: 10.3390/brainsci10090570
|View full text |Cite
|
Sign up to set email alerts
|

A Translational Study on Acute Traumatic Brain Injury: High Incidence of Epileptiform Activity on Human and Rat Electrocorticograms and Histological Correlates in Rats

Abstract: Background: In humans, early pathological activity on invasive electrocorticograms (ECoGs) and its putative association with pathomorphology in the early period of traumatic brain injury (TBI) remains obscure. Methods: We assessed pathological activity on scalp electroencephalograms (EEGs) and ECoGs in patients with acute TBI, early electrophysiological changes after lateral fluid percussion brain injury (FPI), and electrophysiological correlates of hippocampal damage (microgliosis and neuronal loss), a week a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…These findings suggest that CI-1040 could be used acutely to prevent or reduce cytoarchitectonic changes in other spike-associated pathologies, such as those that occur after a TBI. 64 , 65 …”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that CI-1040 could be used acutely to prevent or reduce cytoarchitectonic changes in other spike-associated pathologies, such as those that occur after a TBI. 64 , 65 …”
Section: Discussionmentioning
confidence: 99%
“…Neuronal loss in the hippocampal DG is accompanied by and correlated with an increase of hippocampal neurons excitability after perforant path stimulation one week after TBI [ 34 ]. In our previous study, we reported that spontaneously generated high-amplitude epileptiform hippocampal spike occurrence correlates with increase of microglial cell density and neuronal loss in the hippocampal DG 7 days after TBI [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the corresponding clinical literature highlighting e.g. Komoltsev et al (2020), Kural et al (2020) spike salience is another important parameter used by human experts when detecting epileptogenic activity. The extent to which a spike stands out of the local background can be easily computed, for example, as the ratio of the absolute peak value, h p (t) = c 4 (t), to the standard deviation of the background activity within the time window preceding and succeeding the considered spike time interval.…”
Section: Verbal Description Of a Criterion Expression In Terms Of Spl...mentioning
confidence: 99%